Antropologi Konsumsi: Negosiasi Identitas Muslimah dan Komodifikasi Jilbab Fashion di Lingkungan Kampus IAIN Sultan Amai, Gorontalo - Samsi Pomalingo; Indra Dewi Sery Yusuf; Arfan Nusi (LPPM IAIN Sultan Amai Gorontalo, 2026)
This study aims to examine the dialectic between the regulations of Islamic campus codes of ethics, the pressures of the global trend toward the commodification of the hijab in a modern-secular style, and the persistence of local religious traditions in Gorontalo. The study focuses on an anthropological analysis of consumption to understand how female students at IAIN Sultan Amai Gorontalo (a non-metropolitan area) negotiate their Muslim identity amidst strict institutional moral oversight. The hijab, which originally functioned as a theological instrument, has undergone desacralization through the penetration of market capitalism, giving rise to an “Islamic fashion” subculture and the hijab as a lifestyle commodity signifying economic stratification. This qualitative study, employing an ethnographic design, combines participant observation and semi-structured interviews. Data were analyzed using Pierre Bourdieu’s critical sociological framework (habitus, capital, and field). The findings reveal a tension between institutional rules and visual reality, as well as strategies of “tactical compliance” that give rise to the hybridity of Muslim women’s identities.